2017
DOI: 10.1103/physrevc.95.054328
|View full text |Cite
|
Sign up to set email alerts
|

Complete β -decay pattern for the high-priority decay-heat isotopes I137 and Xe

Abstract: Background An assessment done under the auspices of the Nuclear Energy Agency in 2007 suggested that the β decays of abundant fission products in nuclear reactors may be incomplete. Many of the nuclei are potentially affected by the so called Pandemonium effect and their β-γ decay heat should be restudied using the total absorption technique. The fission products 137 I and 137 Xe were assigned highest priority for restudy due to their large cumulative fission branching fractions. In addition, measuring β-delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 18 publications
3
17
1
Order By: Relevance
“…We found that in the range 300-500 ns the results were stable within 3%. It should be noted that the value we obtain is 14% lower than the value of 7.9(4)% obtained by a similar procedure with MTAS [29]. In view of this discrepancy and the fact that for 95 Rb we also obtain a large difference but of opposite sign, we conclude that further investigations are needed before deciding on the reliability of P n extraction from TAGS spectra [29].…”
Section: Reproduction Of Neutron Interactionscontrasting
confidence: 69%
See 1 more Smart Citation
“…We found that in the range 300-500 ns the results were stable within 3%. It should be noted that the value we obtain is 14% lower than the value of 7.9(4)% obtained by a similar procedure with MTAS [29]. In view of this discrepancy and the fact that for 95 Rb we also obtain a large difference but of opposite sign, we conclude that further investigations are needed before deciding on the reliability of P n extraction from TAGS spectra [29].…”
Section: Reproduction Of Neutron Interactionscontrasting
confidence: 69%
“…It should be noted that the smaller efficiency of DTAS does not affect its performance as a total absorption spectrometer. A nice example is provided by the decay of 137 I which has been measured by DTAS [4] (see also subsection 4.2) and MTAS [29]. Figure 4 in [29] compares the spectrum measured with the full MTAS with the spectrum measured with the sub-detector consisting of the 7 most central modules.…”
Section: Validation Of MC Simulationsmentioning
confidence: 97%
“…For that, the information on this decay available in ENSDF [30] was used as input for the DECAYGEN event generator [51]. This information is reliable according to our TAGS analysis of the β-gated 137 Xe spectrum and is in agreement with the recent TAGS result of B. C. Rasco et al [59]. This procedure avoids the impact of the large statistical fluctuations of the experimental 137 Xe singles spectrum after background subtraction.…”
Section: A Decay Of 137 Isupporting
confidence: 67%
“…These two values are larger than the quoted number in ENSDF: 45.2(5)%. It is also worth mentioning that B. Fogelberg et al [58] reported a β intensity of 47% to the g.s., while the recent TAGS measurement of B. C. Rasco et al determined a value of 49(1)% [59].…”
Section: Nucleusmentioning
confidence: 95%
“…The low-efficiency experimental setups are known to be burdened with a systematic error related to the inability to detect high-energy and low-intensity γ -ray transitions. The total absorption spectroscopy (TAS) measurements, which are not affected by this issue, can significantly reduced the β feedings of the low-lying states [92][93][94][95][96][97][98]. Consequently, the β feedings presented in our work have to be treated as the upper limits while the associated log(f t) values are the lower limits.…”
Section: A Decay Of 66 Mnmentioning
confidence: 98%